Jaringan Saraf Tiruan Dengan Menggunakan Metode Perceptron Mendiagnosa Helminthasis Pada Hewan Kelinci - Rizqaah Saadah Siregar (JURIKOM (Jurnal Riset Komputer), 2020)
Rabbits are mammals from the family Leporidae, which can be found in many parts of the earth. In the past, this animal is a wild animal that lived in Africa to European land. In its development, in 1912, rabbits were classified in the order Lagomorpha. This order is divided into two families, namely Ochtonidea which is good at whistling and Leporidea, including rabbits and hare. The origin of the word rabbit comes from the Dutch language, which is Konijntje which means rabbit cub. This shows that the Nusantara community began to recognize rabbits during the colonia period, whereas on the island of Sumatra there was one species of native Sumatran rabbit Nesolagus Netsheri that was only discovered in the year. In this study artificial neural networks using the perceptron method separately to recognize objects about helminthiasis in rabbits. Helminthiasis lives in the intestinal tract, where digestive enzymes can dissolve eggshells and release worms. Worms begin to multiply by producing more eggs and eventually hatch. Worms have a multicellular structure with organ systems. In this research, perceptron is perceptron trained by using a set of patterns that are given to him repeatedly during training. Each pattern given is a pair of input patterns and the desired pattern as a target. Perceptron do the sum of each input and use the threshold function to calculate the exit. This output is then compared to the desired results, the difference generated from this comparison is used to change the weights in the network. This is done repeatedly until the output is in accordance with the desired results.